Pendampingan Penyusunan Program Bussines Bagi Pengurus Koperasi Desa Merah Putih ( KDMP ) Kecamatan Jombang - Agus Raikhani; linda Ratna sari (Universitas Darul Ulum, 2026)
Village cooperatives play a strategic role in supporting the rural economy, yet many still face challenges in developing business programs. The Merah Putih Village Cooperative, a new cooperative in the community, is one such cooperative that will require management to understand how to plan its business effectively. A well-developed business program will optimize cooperative performance. This community service activity aims to improve the cooperative's management's ability to develop the Merah Putih cooperative's business program. The implementation method includes data collection through interviews and observations, training and evaluation, and ongoing mentoring. The results indicate that the Merah Putih jombang city Village Cooperative management has improved its understanding of business planning, as well as its understanding of the village's potential, enabling it to create more organized, structured, and accurate cooperative plans. Developing a cooperative business plan will help guide the development of the cooperative, achieving optimal results and providing benefits to members and the community. This mentoring activity is expected to improve the knowledge and human resources of the Merah Putih Village Cooperative management, enabling the cooperative to progress and provide added value to the village community.